Students’ Address Forms for Lecturers in Spoken and Written Interactions in Indonesian University Settings: Linguistic Choices and Influencing Factors - Desylva Rima Kumalasari; Dery Tria Agustin (TRANSBAHASA, 2026)
Address terms play an important role in shaping social relationships and communication patterns in educational settings. Despite a growing body of sociolinguistic studies on the use of address terms in communication between students and lecturers in higher education, little research has focused on the forms of address used by Indonesian university students when interacting with their lecturers, either verbally or in writing. This study explores forms of address used by three Indonesian university students, especially those majoring in English language education, when communicating with their lecturers, as well as factors influencing these choices. Data were gathered through semi-structured interviews and the collection of personal documents, including WhatsApp chats, and analyzed following a thematic analytical framework. The findings reveal that students predominantly employed two categories of address terms: Indonesian kinship terms and English honorifics when addressing their lecturers. These choices were influenced by sociocultural settings, personal preferences, students’ perceptions of politeness, and the lack of explicit institutional guidelines. The findings offer insights into the dynamics of student-lecturer interactions in Indonesian higher education, highlighting the complex interplay between language, culture, and power. They also have implications for understanding communication patterns in multicultural and multilingual settings and for informing institutional policies on English language use in higher education.